2020
DOI: 10.1186/s13195-020-00700-8
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cognitive decline trajectories in asymptomatic individuals at risk for AD

Abstract: Background Lack of awareness of cognitive decline (ACD) is common in late-stage Alzheimer’s disease (AD). Recent studies showed that ACD can also be reduced in the early stages. Methods We described different trends of evolution of ACD over 3 years in a cohort of memory-complainers and their association to amyloid burden and brain metabolism. We studied the impact of ACD at baseline on cognitive scores’ evolution and the association between longitudinal changes in ACD and in cognitive score. Results 76.8% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
6
17
0
Order By: Relevance
“…We would like to discuss a recent study on ACD in subjects at risk of preclinical AD, published after our bibliographic search (in October 2020) therefore not included in our review and meta-analysis. This study (Cacciamani et al, 2020 ) describes different trends of evolution of ACD over 3 years in the INSIGHT-PreAD cohort (memory-complainers, Dubois et al, 2018 ) and their association to amyloid burden and brain metabolism. 76.8% of the sample (235 out of 306 subjects) had an accurate ACD (i.e., self-report = informant-report), which remained unchanged over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to discuss a recent study on ACD in subjects at risk of preclinical AD, published after our bibliographic search (in October 2020) therefore not included in our review and meta-analysis. This study (Cacciamani et al, 2020 ) describes different trends of evolution of ACD over 3 years in the INSIGHT-PreAD cohort (memory-complainers, Dubois et al, 2018 ) and their association to amyloid burden and brain metabolism. 76.8% of the sample (235 out of 306 subjects) had an accurate ACD (i.e., self-report = informant-report), which remained unchanged over time.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that poor ACD could serve as an early indicator of AD may seem to run counter to research results on SCD. However, the concepts of SCD and poor awareness are only apparently opposed since they can coexist in the same individual, as found in the INSIGHT-PreAD cohort (Cacciamani et al, 2017(Cacciamani et al, , 2020. This is the case of individuals who complain of a certain degree of cognitive difficulties, still underestimating their severity or impact on daily life (when compared to the assessment made by an informant or using cognitive tests).…”
Section: Introduction Rationalementioning
confidence: 99%
“…Although anosognosia is very common at the clinical stage of AD, recent studies have shown that awareness starts to change even before the AD dementia stage (Folstein et al, 1975;Cacciamani et al, 2017Cacciamani et al, , 2020. Previous research has shown that some individuals may demonstrate heightened awareness of subtle cognitive changes at the preclinical stage, with a subsequent decline of awareness as the individual moves along the AD trajectory (Vannini et al, 2017a(Vannini et al, , 2020Hanseeuw et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous INSIGHT-preAD publications, we argue that such rates of cognitive decline, lower than expected in a population at risk for AD [i.e., SMC plus signs of A β accumulation] is partially explained by the average high education level and cognitive reserve of the INSIGHT-preAD participants, a cohort in which potential compensatory mechanisms have already been reported ( Babiloni et al, 2020 ;Dubois et al, 2018 ;Gaubert et al, 2019 ). This cohort is mainly represented by people who still engage in small post-retirement works, continuous social and intellectual activity ( Babiloni et al, 2020 ;Cacciamani et al, 2020 ;Dubois et al, 2018 ).…”
Section: Potential Utilization Of Pls-vip Approch In Resilience Studiesmentioning
confidence: 86%